Students’ Perceptions of Green Chemistry in a Project-Based Learning (PjBL) Model Integrated with Local Culture - Simanjuntak, Familia Novita; Candra Ditasona; Sri Rejeki Ignasia Sitohang; Angelia Patricia Situmorang (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The purpose of this study is to examine how students see studying green chemistry using a culturally integrated project-based learning (PjBL) approach. This study used a qualitative descriptive methodology and was carried out at Don Bosco High School in Jakarta. A saturation sampling strategy was used to choose a sample of 35 tenth-grade science students. Students' written reflections after the PjBL exercises and observations made during the learning process were used to gather data. Data reduction, data presentation, and conclusion drawing were the phases of data analysis. The study's findings show that students' perspectives of studying chemistry have changed from being initially seen as challenging and abstract to being more relevant and significant. While some difficulties with group cooperation were still noted, the majority of students showed active involvement and positive responses throughout the learning process, as evidenced by increased interest, curiosity, and participation in project activities. More than half of the students selected the composting project as their final result, and they were able to connect it to actual environmental problems, especially how organic waste is managed in everyday life and cultural customs. These results show that the use of culturally integrated PjBL promotes collaborative and relevant learning experiences in addition to giving students a more practical understanding of green chemistry principles. As a result, this teaching approach helps students develop more favorable opinions of chemistry and strengthens the link between scientific ideas and practical applications.